An alternative distraction osteogenesis method for atrophic posterior mandible: Case report - Deniz, Kagan; Uckan, Sina; Senel, Firdevs (Annals of Medical Research, 2021)
None
Keywords: Transport distraction osteogenesis; mandible; alveolar bone